C Program Verication in the Multilanguage System Spectrum - V. A. Nepomniashy; I. S. Anureev; M. M. Atuchin; I. V. Maryasov; A. A. Petrov; A. V. Promsky (Моделирование и анализ информационных систем)
This paper presents the expendable multi-language analysis and verication system SPECTRUM, which is being developed within the framework of the project SPEC- TRUM. The project prospects are discussed using the example of C program verication. The project aims at the development of a new integrated approach to program verica- tion which will allow the integration, unication and combination of program verication techniques together with accumulation and reuse of knowledge about them. One of the project features consists in the use of the specialized executable specication language Atoment. This language provides a unied format to represent both verication meth- ods and data for them (program models, annotations, logic formulas). The C-targeted component of the SPECTRUM system is based on our two-level C program verication method. This method represents a good illustration of the integrated approach, since it provides a complex C program verication that combines operational, axiomatic and transformational approaches.